SEVERE INTRUSIVE LUXATION OF TWO IMMATURE PERMANENT INCISORS - A CASE REPORT - Mihaela Tănase; Cristina-Crenguța Albu; Anca Ilincescu; Aneta Munteanu; Ioana-Andreea Stanciu (Romanian Society of Oral Rehabilitation, 2024)
Antibioprofilaxia non-chirurgicalaTraumatic dental injuries of immature permanent teeth represent an emergency in pediatric dentistry practice, affecting one third of children up to 12 years old. Intrusive luxation is a severe periodontal trauma, the tooth is partially or totally dislocated into the alveolar bone and may also be associated with a crown fracture. This tooth injury can have various short and/or long term complications, such as pulp necrosis with/ without pathologic root resorption. In these cases, regenerative endodontic procedures such as revascularization have a good prognosis and are considered an alternative to apexification. This case report describes the challenges in managing severe complicated intrusive luxations in two immature permanent incisors.